Generative artificial intelligence in primary care: an online survey of UK general practitioners - Charlotte R Blease; Cosima Locher; Maria Hägglund; Jens Gaab; Kenneth D Mandl (BMJ Health & Care Informatics)
Objectives Following the launch of ChatGPT in November 2022, interest in large language model-powered chatbots has soared with increasing focus on the clinical potential of these tools. We sought to measure general practitioners’ (GPs) current use of this new generation of chatbots to assist with any aspect of clinical practice in the UK.Methods An online survey was distributed to a non-probability sample of GPs registered with the clinician marketing service Doctors.net.uk. The study was launched as a monthly ‘omnibus survey’ which has a predetermined sample size of 1000 participants.Results 531 (53%) respondents were men, 544 (54%) were 46 years or older. 20% (205) reported using generative artificial intelligence (AI) tools in clinical practice; of those who answered affirmatively and were invited to clarify further, 29% (47) reported using these tools to generate documentation after patient appointments and 28% (45) to suggest a differential diagnosis.Discussion Administered a year after ChatGPT was launched, this is the largest survey we know of conducted into doctors’ use of generative AI in clinical practice. Findings suggest that GPs may derive value from these tools, particularly with administrative tasks and to support clinical reasoning.Conclusion Despite a lack of guidance about these tools and unclear work policies, GPs report using generative AI to assist with their job. The medical community will need to find ways to both educate physicians and trainees and guide patients about the safe adoption of these tools.